2011
DOI: 10.2214/ajr.10.4671
|View full text |Cite
|
Sign up to set email alerts
|

CT-Guided Sclerotherapy With Ethanol Concentration Monitoring for Treatment of Renal Cysts

Abstract: Our in vitro experiment showed a linear correlation between ethanol concentration and CT density values. CT density values can be used to measure ethanol concentration. Ethanol concentration monitoring during the procedure can improve the success rate in CT-guided sclerotherapy for simple renal cysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…The mean Hounsfield value of 99.9% ethanol did decrease to -190 Hounsfield units (HU) and there was a linear correlation between ethanol concentration and Hounsfield values in our previous study (5). This suggests that monitoring of the HU of ethanol by computed tomography (CT) may be an effective method in ethanol sclerotherapy of renal cysts.…”
Section: Introductionmentioning
confidence: 60%
See 4 more Smart Citations
“…The mean Hounsfield value of 99.9% ethanol did decrease to -190 Hounsfield units (HU) and there was a linear correlation between ethanol concentration and Hounsfield values in our previous study (5). This suggests that monitoring of the HU of ethanol by computed tomography (CT) may be an effective method in ethanol sclerotherapy of renal cysts.…”
Section: Introductionmentioning
confidence: 60%
“…Second, the concentration of ethanol in the cyst after the 2-hour retention was diluted to below the level of the coagulating effect on the cyst epithelium. The mean Hounsfield value of 99.9% ethanol went down to -190 HU (5). In our study, we observed that the aspirated cyst fluid was clear at the beginning, but the aspirated liquid became cloudy after the injection of ethanol.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations